FAKTOR RISIKO INSIDENSI DIABETES MELLITUS TIPE 2 DI WILAYAH KERJA PUSKESMAS PEMBINA PALEMBANG - Esti Sri Ananingsih; Michelle Salsabilah; Hendawati Hendawati; Faiza Yuniati; Intan Kumalasari; Sinta Octaviana (JPK : Jurnal Penelitian Kesehatan, 2026)
Type 2 diabetes mellitus (T2DM) is a major global health issue characterized by increasing morbidity, mortality, and family burden. Unhealthy lifestyles, excessive fast food consumption, lack of physical activity, age, family history, and smoking habits are known risk factors. The study aimed to investigate the risk factors for the incidence of type 2 diabetes mellitus in the working area of Pembina Community Health Center (Puskesmas Pembina), Palembang, in 2025. The study is a cross-sectional study with patients visiting the General Medicine Clinic of Puskesmas Pembina, Palembang in 2025 as the population. A total of 79 respondents were selected from this population using accidental sampling approach. The study revealed that there is significant correlations between age (p-value = 0.000), smoking habits (p-value = 0.009), physical activity levels (p-value = 0.026), and dietary patterns (p-value = 0.048) and the incidence of type 2 diabetes mellitus. However, there is no significant correlations were found between gender (p-value = 0.135) and family history (p-value = 0.695) with the incidence of T2DM. Based on the results of this study, it can be concluded that age, smoking habits, physical activity, and dietary patterns are risk factors for the incidence of type 2 diabetes mellitus in the working area of Puskesmas Pembina Palembang.